Sistem Rekomendasi Pencarian Tempat Wisata Kota Batang Menggunakan Haversine - Arningtya, Luthfi Arningtya; Amin, Imam Husni Al (LPPM UNIKA Santo Thomas Medan, 2023)
Batang City has many tourist attractions, but most people only visit a few places, so many other tourist attractions in Batang City are rarely visited and less exposed. In the current era of rapidly developing technology, recommendation systems are needed in all fields, especially or especially in finding locations such as finding the closest tourist destination to the user's position in the city of Batang. This study aims to create a recommendation system for searching for tourist attractions in Batang City that can display two Batang City tours from the closest distance to the user using the haversine method and displaying tourist details in Batang City which consists of the name of the tourist spot, the distance from the user's location to the tourist spot, address, telephone number and description of the selected Batang city tourist attractions.